The Evolution of the Legal Framework of Consumer Credits in the European Union - Dudaš, Atila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
The beginning of the evolution of the regulatory framework of consumer credits in the European Union is hallmarked by the adoption of Directive No. 87/102/ЕЕC. Later, a wide range of directives were adopted gradually, regulating specific segments of retail banking, having relevance in terms of legal protection of consumers and of the need to facilitate cross-border banking transactions and credit activities, on the one hand, and relating to cross-border investments, on the other. Directive No. 87/102/ЕЕC was repealed by Directive No 2008/48/ЕU on consumer credit contracts. It introduced major changes into the legal framework of consumers credits. The most notable novelties are the creditors’ duty to indicate all interests and costs related to the credit by the mechanism of the annual percentage rate of charge and to provide clear and prominent precontractual information to the consumer by the means of ESIS. The beginning of the last phase in the evolution of the regulatory framework of consumer credits is marked by the adoption of Directive No 2014/17/ ЕU, known in professional circles as the Mortgage Credit Directive. Its adoption was considerably influenced by the experience of the recent global economic crisis and the crisis of residential mortgage credits as its consequence, and unfair practice of banks in applying variable interest rates. Hence, the creditors’ precontractual duties are amplified, the rules on the APR and providing precontractual information to the consumer by the means of ESIS are devised based on the principle of maximal harmonization, rules on foreign currency loans and variable interest loans are introduced, etc. However, there are well-argued doubts expressed in the doctrine about the potential of the Directive to achieve its goals of creating a single European mortgage credit market and achieving uniform level of consumer protection in mortgage loans in the European Union. Namely, the provisions of the Directive, with the exception of the rules on APR and the pre-notification of consumers by the means of ESIS, are based on the principle of minimum harmonization. Therefore, it is to be expected that the transposition of the Directive in national legal systems will not be uniform, rendering the realization of a single legal regime of mortgage consumer credits in the European Union virtually impossible.